Formação-Arte-Escrita: contribuições estéticas para a noção de experiência - Braga, Jonathan Taveira [UNESP] (2014)
Seeking to contribute to the aesthetic dimension of formation – from the perspective of the experience and as the process of producing subjectivities beyond the formal spaces of education –, this study approaches visual artist Ricardo Basbaum‟s life and creative trajectory through cartographic practice. How do Basbaum's trajectory, processes and practices contribute to the production of thoughts about other existential territories? This question circumvents the challenge of seeking contemporary artistic and inventive processes for investigating procedures that focus on policies of subjectivation: dimensions of the sensitive, present in the way one relates to the world; possibilities of singularization compared with capture and modulation devices; settings of modes of existence articulated with writing practices as an experience in itself. In addition to the literature review that mapped the referred concepts, this work was comprised of the following materials of analysis: Basbaum's testimonials on his educational path and work processes (one collected in audio form and others found in different printed and virtual media); websites maintained by the artist himself, which document his projects through various images and writings; some experiences in collective exhibitions that he participated in and materials available in these events such as posters, photographs and diagrams